Acute pyelonephritis in pregnancy and plasma syndecan-1: evidence of glycocalyx involvement. (31st December 2023) - Immonen, Timothy; Jung, Eunjung; Gallo, Dahiana M.; Diaz-Primera, Ramiro; Gotsch, Francesca; Whittaker, Peter; Than, Nandor Gabor; Bosco, Mariachiara; Tarca, Adi L.; Suksai, Manaphat; Romero, Roberto; Chaiworapongsa, Tinnakorn
Abstract: Background: Acute pyelonephritis, a risk factor for maternal sepsis, adult respiratory distress syndrome, and preterm labor, is a frequent cause of hospitalization. This condition is characterized by excessive intravascular inflammation and endothelial cell activation and dysfunction. Syndecan-1, a major component of the glycocalyx, is a gel-like layer that covers the luminal surface of healthy endothelial cells, preserving and mediating many endothelial functions. During pregnancy, there is an additional potential source of syndecan-1, the "syncytiotrophoblast glycocalyx, " which lines the intervillous space. Insults that damage the glycocalyx lead to a shedding of syndecan-1 into the circulation. Hence, syndecan-1 has been proposed as a marker of endothelial injury in conditions such as sepsis, trauma, cardiovascular disease, and diabetes mellitus. Objective: The objective of this study was to determine whether the plasma syndecan-1 concentration changes in women with acute pyelonephritis in the presence or absence of bacteremia. Study design: This cross-sectional study included three groups: (1) non-pregnant women ( n = 25); (2) women with an uncomplicated pregnancy from whom samples were collected preterm ( n = 61) or at term ( n = 69); and (3) pregnant women diagnosed with acute pyelonephritis from whom samples were collected at the time of diagnosis during the second and third trimesters ( n = 33). The diagnosis of acute pyelonephritis was based on clinical findings and a positive urine culture for bacteria. Blood culture results were available in 85% (28/33) of women with acute pyelonephritis. Plasma concentrations of syndecan-1 were determined by a validated immunoassay. Results: ( 1) Women with an uncomplicated pregnancy had a higher plasma concentration of syndecan-1 than non-pregnant women. The geometric mean (95% confidence interval [CI]) of syndecan-1 concentration was 51.0 (12.1–216.1) ng/mL in non-pregnant controls; 1280 (365–4487) ng/mL in normal preterm gestations; and 1786 (546–5834) ng/mL in normal term gestations (adjusted p < .005 for all three between group comparisons); ( 2) plasma syndecan-1 concentrations increased with gestational age among women with a normal pregnancy ( p < .001, R 2 = 0.27); (3) syndecan-1 multiple of the mean (MoM) values in pregnant patients with acute pyelonephritis were higher than those in normal pregnant women based on second- and third-trimester samples ( p = .048, 1.26-fold change). The increase was driven primarily by cases with a positive blood culture ( p = .009, 1.74-fold change); (4) when data from third-trimester samples were compared, overall differences in syndecan-1 MoM values between cases and controls were slightly larger ( p = .03, 1.36- fold change), which were especially contributed to by cases with a positive blood culture ( p = .023, fold change 1.79-fold change). Conclusions: Plasma syndecan-1 concentration is higher in pregnant women and increases as a function of gestational age. Patients with acute pyelonephritis have a higher plasma concentration of syndecan-1, and this is particularly the case in the presence of bacteremia.